Dari Ritual ke Realitas Virtual (Tinjauan Video Komersial Seni Pertunjukan Tradisi Yang Beredar di Bandung) - Agus Djatnika (Jurnal Rekarupa, 2011)
ABSTRACT The ease and convenience offered by technology, especially for the audio-video recording has penetrated the tradition performance art and has become an offer that enriches the treasury of the cultural tradition itself. The trend appears in the tradition  performance art in different regions in Indonesia especially in Java, although the aspects of the production process seems to be amateurish as it is still limited to only a recording of an art performance event during the show. In addition, it is not specifically prepared for a production. The distribution of the tradition art performance video is accepted by the community with a tendency to be getting more and more in types as well as the choices of the tradition performance art among the commercial video markets. The goal diversity of the tradition performance art video launches in the markets ranging from the goal of a conventional business opportunity, a tradition art promotion, to a video recording studio promotion has become the parts of the diversity itself. Documenting the tradition performance art has become one of the cultural advantages which is very invaluable and has emerged from the community itself. These symptoms will be more culturally valuable if coupled with the seriousness of the video makers professionally completed with a narrative that contains all information about the distributed tradition performance arts and finally the society can be invited to be more intelligent appreciators. Keywords: technology, performance art, tradition Abstrak Kemudahan dan kepraktisan yang ditawarkan teknologi, khususnya perekaman  dalam bentuk audio-video merambah pada seni pertunjukan tradisi, dan  menjadi  sebuah tawaran yang memperkaya  perbendaharaan budaya tradisi itu sendiri. Kecenderungan ini muncul pada seni pertunjukan tradisi di berbagai daerah di Indonesia khususnya di Jawa, meskipun dari aspek  proses produksi terkesan amatiran karena hanya sebatas  perekaman suatu peristiwa. saat seni pertunjukan itu berlangsung,  dan tidak secara  khusus dipersiapkan untuk  diproduksi. Peredaran video seni pertunjukan tradisi disambut baik oleh masyarakat dengan kecenderungan makin marak jenis maupun pilihan seni pertunjukan tradisidi tengah pasar video komersial. Keragaman tujuan peluncuran video seni pertunjukan  tradisi di pasaran mulai dari tujuan kesempatan bisnis  konvensiona, promosi kelompok seni tradisi hingga promosi studio rekaman video menjadi bagian dati keragaman tersebut. Pendokumentasian seni pertunjukan tradisi jadi salah satu manfaat budaya yang tidak ternilai dan muncul dari masyarakat itu sendiri. Gejala ini bisa lebih bernilai budaya bila dibarengi dengan kesungguhan para pembuat video secara professional dibarengi dengan narasi yang berisi informas tentang seni pertunjukan tradisi yang diedarkan tersebut yang pada akhirnya masyarakat sebagai aprisiator diajak lebih cerdas. Kata Kunci: teknologi, seni pertunjukan, tradisi